1996
DOI: 10.1002/(sici)1096-9063(199604)46:4<381::aid-ps373>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Phenmedipham-Ozone Pollution Interactions in Sugarbeet (Beta vulgarisL. cv. Saxon): A Physiological Study

Abstract: Actively growing sugarbeet is treated with the post-emergent herbicide phenmedipham at times when ozone pollution episodes are likely to occur. There is a possibility of an interaction occurring between ozone and phenmedipham as both treatments produce similar effects in susceptible plants, such as a reduction in growth and photosynthesis and an increase in the activities of endogenous antioxidant enzymes. To investigate this likelihood, laboratory experiments were conducted in which two-to three-leaf sugarbee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Antioxidant metabolism is considered to be a critical component in plant responses to O 3 stress. Activities of antioxidant enzymes such as peroxidase and glutathione reductase are often increased by O 3 (Dixon et al 1996; Burkey et al 2000; Chen and Gallie 2005; Cheng et al 2006; US EPA 2006). In addition, the antioxidant compound most studied in this regard is ascorbic acid (vitamin C).…”
Section: Ozone Toxicity and Developmental Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Antioxidant metabolism is considered to be a critical component in plant responses to O 3 stress. Activities of antioxidant enzymes such as peroxidase and glutathione reductase are often increased by O 3 (Dixon et al 1996; Burkey et al 2000; Chen and Gallie 2005; Cheng et al 2006; US EPA 2006). In addition, the antioxidant compound most studied in this regard is ascorbic acid (vitamin C).…”
Section: Ozone Toxicity and Developmental Effectsmentioning
confidence: 99%
“…Previous studies have suggested that O 3 can influence the efficacy of some agricultural chemicals, depending on exposure protocols, plant sensitivity to the herbicide and O 3 , O 3 concentrations and other environmental factors such as light intensity (Dixon et al 1996). Herbicides that induce the formation of toxic levels of ROS in plants may be less effective in situations where O 3 has stimulated antioxidant metabolism, which increases their resistance to the herbicide effect (Dixon et al 1996).…”
Section: Ozone Interactions With Herbicide Efficacy and Invasive Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fungicides stress:-A number of agricultural chemicals such as fungicides (91) and herbicides (92) have been shown to possess antiozonant properties. However, most of these investigations have concentrated on the effectiveness of agrochemicals in preventing plants from ozone injury, and relatively little work has focused on the physiological and biochemical modes of action.…”
Section: Environmental Stresses Impact:-mentioning
confidence: 99%